2008
DOI: 10.1088/0957-4484/20/2/025605
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of dendritic Au@Pt core–shell nanomaterials for use as an effective fuel cell electrocatalyst

Abstract: We report the controlled synthesis of dendritic Au@Pt core-shell nanomaterials. The size and morphology of the Au cores and the Pt shell thickness of the Au@Pt core-shell nanostructures could be easily tuned. It was found that the directing agent and the reducing agent play critical roles in the synthesis of dendritic Au@Pt core-shell nanomaterials. For comparison purposes, conventional Au@Pt core-shell nanoparticles and monometallic Pt nanoparticles were also synthesized by the successive reduction method. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 32 publications
3
73
1
1
Order By: Relevance
“…This finding is in excellent agreement with several earlier reports that have clearly indicated that bimetallic nanoparticles exhibit an enhanced electro-catalytic activity compared with pure metal nanoparticles. [17][18][19] A similar behavior was also reported for multicomponent systems formed of graphene sheets decorated with bimetallic nanoparticles. 20 In their recent work, Hu et al 21 demonstrated that graphenebimetallic Pt-Au nanoparticles exhibited an enhanced electro-catalytic activity, compared with Au-graphene or Pt-graphene.…”
Section: S-captopril 1-(3-mercapto-2-(s)-methyl-1-oxopropyl)-s(l)supporting
confidence: 76%
“…This finding is in excellent agreement with several earlier reports that have clearly indicated that bimetallic nanoparticles exhibit an enhanced electro-catalytic activity compared with pure metal nanoparticles. [17][18][19] A similar behavior was also reported for multicomponent systems formed of graphene sheets decorated with bimetallic nanoparticles. 20 In their recent work, Hu et al 21 demonstrated that graphenebimetallic Pt-Au nanoparticles exhibited an enhanced electro-catalytic activity, compared with Au-graphene or Pt-graphene.…”
Section: S-captopril 1-(3-mercapto-2-(s)-methyl-1-oxopropyl)-s(l)supporting
confidence: 76%
“…A practical approach, combining different metals with Pt have widely been adopted to reduce the amount of Pt and improve its activity and durability. Among those, Au is one of the interesting metals due to its superior oxygen-reduction-reaction activity and durability reported in Pt-Au nanostructures, where the Pt (shell)-Au (core) structures and the effect of Au decoration on the edges of Pt surfaces are used as a fuel cell catalyst [1][2][3][4][5]. Hence, it is essential to understand the local structures of both Pt and Au in an atomic scale to elucidate the mechanism of the catalytic reactions in Pt-Au nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…2 O 溶于水 并定容成 100 mL 溶液, 取其中 1.88 mL 加 30 mL 水稀 释. 在冰水浴和磁力搅拌(@750 r/min)条件下, 加入 10 mL 的 0.02 mol/L Na 3 Cit [41] , 然后在 15 min 内滴加 6.1 mL 新鲜配制的 0.01 mol/L NaBH 4 . 继续在室温下搅拌 (@1200 r/min) 12 h 以确保残余的 NaBH 4 分解.…”
unclassified